2020
DOI: 10.1038/s41598-020-57680-w
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of cysts and capillary non perfusion areas in diabetic macular edema using two different OCTA devices

Abstract: the aim of this paper was to distinguish the appearance of cysts and non-perfusion areas (npAs) in diabetic macular edema (DME) using two different Optical Coherence Tomography Angiography (OCTA) devices. in this study, patients underwent octA using the AngioVue XR Avanti Spectral Domain (SD) OCTA and the PLEX Elite 9000 Swept-Source (SS) OCTA. Foveal and extrafoveal regions of interest (ROI), defined as any area with an altered flow signal comparing to the surrounding retina, were selected in superficial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The presence of cystoid spaces in chronic diabetic macular edema may resemble areas of capillary nonperfusion on enface OCTA since both may appear as black or grey areas [68,69]. The appearance of these areas, however, can be variable depending on which OCTA machine is used [69,70].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…The presence of cystoid spaces in chronic diabetic macular edema may resemble areas of capillary nonperfusion on enface OCTA since both may appear as black or grey areas [68,69]. The appearance of these areas, however, can be variable depending on which OCTA machine is used [69,70].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…It was demonstrated that parameters derived from different devices are not necessarily equivalent due to different applied wavelengths and algorithms for perfusion detection [ 34 ]. In a recent study SSPiM were detected more frequently detected using the Plex Elite 9000 than the Optovue OCT-A [ 35 ]. Therefore the number of detected artifacts in our patient cohort may be higher if comparing it with other SS-OCTA devices.…”
Section: Discussionmentioning
confidence: 99%
“…We also obtained the en face OCTA images of the SCP and DVC slabs at the instrument's default setting [37]. These images were exported and then imported into Fiji distribution of ImageJ as 1024 × 1024 pixels images [29].…”
Section: Methodsmentioning
confidence: 99%